THE EVOLUTION OF FACIAL IDENTIFICATION IN THE JUDICIAL SYSTEM - Ciochină, Claudiu-Dănuț (International Journal of Legal and Social Order, 2025)
Facial identification has had a crucial role in forensics, helping to modernize justice investigation and administration methods. Starting with Alphonse Bertillon’s anthropometry in the 19th century and implementing complex biometric systems such as the facial identification and recognition System (NBIS), this technology has evolved significantly. We propose to examine the transition from manual methods to automated identification systems, pointing out both their advantages and their limitations, as well as the international collaborations that have eased the global use of biometric data.